The New Jew in Film – Exploring Jewishness and Judaism in Contemporary Cinema - Tal, Tzvi (Imagofagia, 2021)
Sobre Abrams, Nathan. The New Jew in Film – Exploring Jewishness and Judaism in Contemporary Cinema. London: I.B. Tauris, 2012, 258 pp., ISBN 9781848555755 Palabras clave: reseña, Abrams, Nathan, . The New Jew in Film – Exploring Jewishness and Judaism in Contemporary Cinema